2022
DOI: 10.5603/cj.a2021.0110
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of PCSK9 inhibition in cardiovascular disease: a meta-analysis of 45 randomized controlled trials

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Cardiology Journal" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…The meta-analysis showed that PCSK9 inhibitors increased the expression of high-density lipoproteins (approximately 5.63–7.05%). However, the protective effect on lipoprotein A1 has not been confirmed through randomized controlled trials [ 44 ]. In addition, several large cohort studies have demonstrated the pheMR results of PCSK9 [ 39 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis showed that PCSK9 inhibitors increased the expression of high-density lipoproteins (approximately 5.63–7.05%). However, the protective effect on lipoprotein A1 has not been confirmed through randomized controlled trials [ 44 ]. In addition, several large cohort studies have demonstrated the pheMR results of PCSK9 [ 39 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Эффективность МАТ в снижении ХС-ЛНП, выраженная в средней разнице между исходным значением и конечным, для алирокумаба составляет 51,29%, для эволокумаба -53,99% [84]. Эти данные были получены в метаанализе 45 РКИ длительностью от 8 до 134 нед.…”
Section: Discussionunclassified
“…Proprotein convertase subtilisin/kexin type 9 (PCSK9) increases plasma low-density lipoprotein cholesterol (LDL-C) by decreasing expression of the LDL receptor on hepatic cells, alirocumab and evolocumab bind selectively to circulating PCSK9, preventing its interaction with the LDL receptor [14,39]. PCSK9 inhibitors affect the entire lipid profile: could significantly reduce low-density lipoprotein cholesterol, total cholesterol, triglycerides and increase high-density lipoprotein cholesterol [15]. Many studies have noted a beneficial effect on lipid metabolism and a reduction in cardiovascular mortality [16].…”
Section: Monoclonal Antibodies Blocking Pcsk9 Actionmentioning
confidence: 99%